2009
DOI: 10.1002/ps.1733
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of clomazone in the soil environment

Abstract: The results indicate that clomazone does not sorb appreciably to sandy or clay soils. Its sorption affinity and capacity is greater in humic acid, and consequently clomazone has difficulty desorbing from soil organic matter. Sorption appears to follow processes explained by the dual-mode model, the presence of fire residues (black carbon) and a recently proposed sorption mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
2
25
4
Order By: Relevance
“…9 mg/kg of 14 Cclomazone sorbed to a silty clay loam soil; such sorption was independent of temperature, and soil moisture content had a minor sorbtive effect. Although overall soil sorption is low, the agent has a higher affinity for binding to humic acid than to whole soil (Gunasekara et al 2009). …”
Section: Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…9 mg/kg of 14 Cclomazone sorbed to a silty clay loam soil; such sorption was independent of temperature, and soil moisture content had a minor sorbtive effect. Although overall soil sorption is low, the agent has a higher affinity for binding to humic acid than to whole soil (Gunasekara et al 2009). …”
Section: Soilmentioning
confidence: 99%
“…Furthermore, it appears that the presence of black carbon or burned residues, in fire-affected locations, increase the sorption of this herbicide (Gunasekara et al 2009). Loux et al (1989) determined that adsorption was dictated by organic matter rather than by clay content; K d values for clomazone ranged from 0.47 for silt loam to 5.3 for loamy sand.…”
Section: Soilmentioning
confidence: 99%
“…Some studies using clomazone in different soils over the world have related its sorption with soil organic matter contents (Gunasekara et al, 2009;Umiljendiae et al, 2013), which explains symptom absence in Organosol, with lower herbicide leaching. In the other substrates that presented lower organic matter levels, the other attribute that must be considered is clay content, as reported by Monquero et al (2008).…”
Section: Resultsmentioning
confidence: 99%
“…Bortoluzzi et al (2006) found the presence of this product in surface water adjacent to tobacco crops. The presence of clomazone in water and soil samples have been reported in the literature not only in Brazil but also in other countries such as Spain (Nevado et al, 2007), Italy (Palmisano & Zambonin, 2000), China (Li et al, 2010), Uruguay (Carlomagno et al, 2010) and United States (Gunasekara et al, 2009). …”
Section: Herbicides -Properties Synthesis and Control Of Weeds 152mentioning
confidence: 87%